Violence against women: a reading from gender economics - Cadena-Palacios, Raúl (2014)
This paper intends to present the main obstacles limiting micro entrepreneurship in Ecuador from a reading of the economics of gender; for which it is considered as the main variable, domestic violence, especially those carried out against women. In this order, some statistics that show the gender bias is present; and secondly, we study its repercussions on the development agenda within the national plan for the good life.